Joint toxic effects of phoxim and lambda-cyhalothrin on the small yellow croaker (Larimichthys polyactis). (November 2022) - Zhan, Wei; Weng, Hongbiao; Liu, Feng; Han, Mingming; Lou, Bao; Wang, Yanhua
Abstract: Although pesticides commonly exist as combinations in real-life situations of the aquatic ecosystem, the impact of the toxicity of their mixtures has remained largely unclear. In this study, we investigated the combined effects of two neurotoxic pesticides, including one organophosphate insecticide phoxim (PHO) and one pyrethroid insecticide lambda -cyhalothrin (LCY), on the embryos of the small yellow croaker ( Larimichthys polyactis ), and their potential pathways. LCY exhibited higher toxicity relative to PHO, with a 72-h LC50 value of 0.0074 mg a.i. L −1, while the corresponding value for PHO was 0.12 mg a.i. L −1 . The mixture of PHO and LCY exerted a synergistic effect on the embryos of L. polyactis . The activities of antioxidant enzyme CAT and apoptotic enzyme caspase 3 were substantially changed in most single and combined exposure groups relative to the baseline value. Under both single and combined exposures, more significant changes were found in the mRNA expression of five genes, including the immunosuppression gene ngln2, the apoptosis gene P53, the endocrine system gene cyp19a1b, as well as neurodevelopment genes of ap and acp2, relative to the baseline value. Furthermore, the non-target metabolomic analysis demonstrated that hundreds of differential metabolites, including two bile acids (taurodeoxycholic acid and tauroursodeoxycholic acid), were significantly increased in the exposure groups. The bile acids were closely associated with the gut microbiota, and 16S rRNA sequencing results demonstrated dysfunction of the gut microbiota after exposure, especially in the combined exposure group. Our findings indicated that there might be a potential risk connected to the co-occurrence of these two pesticides in aquatic vertebrates. Consequently, future ecological risk assessments should incorporate synergistic mixtures because the current risk assessments do not consider them. Graphical abstract: Image 1 Highlights: Lambda -cyhalothrin in combination with phoxim presented synergistic acute toxicity. Expression levels of 5 genes in mixtures elicited greater changes than individuals. More metabolites were discovered after mixture exposure than individual exposures. Co-exposure caused most significantly varied microbiota at phylum and genus levels. Synergistic effects should be incorporated into risk assessment of pesticide.